2019
DOI: 10.3390/microorganisms7120700
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Kombucha Obtained from Green, Oolong, and Black Teas on Inhibition of Pathogenic Bacteria, Antioxidation, and Toxicity on Colorectal Cancer Cell Line

Abstract: Kombucha tea is a refreshing beverage that is produced from the fermentation of tea leaves. In this study, kombucha tea was prepared using 1% green tea, oolong tea, and black tea, and 10% sucrose with acetic acid bacteria and yeast. The pH values of the kombucha tea were found to be in a range of 2.70–2.94 at 15 days of fermentation. The lowest pH value of 2.70 was recorded in the kombucha prepared from black tea. The total acidity of kombucha prepared from black tea was the highest by 16.75 g/L and it was sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 42 publications
5
86
2
10
Order By: Relevance
“…According to Vitas et al [30], the decrease in pH values in the culture medium is an indicator of the activity of kombucha microbial cultures on substrates. This effect has previously been reported in some studies using white, red, black, green, and oolong tea-based culture media [39,40]; as well as in some herbal extracts (e.g., winter savory, peppermint, stinging nettle, wild thyme, elderberry, and quince) and has been associated with the metabolism of sugars in organic acids by bacteria and yeasts during the fermentation process [28].…”
Section: Ph Tss and Tasupporting
confidence: 64%
See 1 more Smart Citation
“…According to Vitas et al [30], the decrease in pH values in the culture medium is an indicator of the activity of kombucha microbial cultures on substrates. This effect has previously been reported in some studies using white, red, black, green, and oolong tea-based culture media [39,40]; as well as in some herbal extracts (e.g., winter savory, peppermint, stinging nettle, wild thyme, elderberry, and quince) and has been associated with the metabolism of sugars in organic acids by bacteria and yeasts during the fermentation process [28].…”
Section: Ph Tss and Tasupporting
confidence: 64%
“…(Orion Star™ A215, ThermoFisher Scientific TM , Waltham, MA, USA) [3,39]. On the other hand, the content of total soluble solids (TSS) was determined using an analogous hand refractometer (Atago Co., Ltd., Nonthaburi, Thailand) and the results were expressed in • Brix [40]. Finally, titratable acidity (TA) was determined based on previous studies [28,38] with some modifications.…”
Section: Determination Of Ph Total Acidity and A Total Of Soluble Solidsmentioning
confidence: 99%
“…Several additional previous studies proved that kombucha of fermented black tea exerts antibacterial activity against a broad spectrum of bacteria [ 19 , 42 , 43 , 44 ]. Kaewkod et al [ 45 ] found that the kombucha prepared from different types of tea (green, oolong and black) after 15 days of fermentation had efficient inhibitory activity on all pathogenic enteric bacteria tested: E. coli O157:H7 DMST 12743, Shigella dysenteriae DMST 1511, Salmonella typhi DMST 22842, and Vibrio cholerae .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Greenwalt et al [ 42 ] showed that the antimicrobial activity of kombucha against pathogenic microorganisms is largely attributable to acetic acid. Organic acid molecules could induce cytoplasmic acidification and destroy bacterial cells [ 45 ]. The antibacterial activity exerted by kombucha compounds might also be interpreted on the basis of osmotic pressure of the solutes which existed in the hypertonic medium in relation to the outer aquatic medium; this facilitates the diffusion of the bioactive materials from cell membranes via the selective permeability.…”
Section: Discussionmentioning
confidence: 99%
“…They conclude that some extracts with relevant antibacterial and antioxidant activity could have potential for use as both antibiotic alternatives in animal feeding and as a natural food preservative in the food industry. Kaewkod et al [8] report the study of different biological properties of Kombucha tea from various kinds of tea leaves including green, oolong, and black tea. They observe that the extent of the antibacterial effect against several foodborne pathogens was related with the amount of organic acids in the beverage, indicating the great potential health benefits of Kombucha tea.…”
mentioning
confidence: 99%